POSTFIRE RESPROUTING OF SHRUBBY SPECIES IN MEDITERRANEAN MAQUIS (VEGETATIO, 1991)
The vegetative resprouting of mediterranean maquis shrubby species was examined eight years after fire. Post-fire regeneration occurs through the resprouting of stumps. All species (Quercus ilex L., Phillyrea latifolia L., Arbutus unedo L., Erica arborea L., Pistacia lentiscus L.) show a rapid growth in the first years after fire, and a decrease already from 4th-5th year. All the species survived the fire and reconstituted a community similar to that unburned in a relatively short time span.